Colubrina javanica Miq. (Rhamnaceae) A new angiosperm record for Bangladesh - Rahman, Mohammad Sayedur; Hossain, Gazi Mosharof; Khan, Saleh Ahammad; Uddin, Sarder Nasir (Bangladesh Journal of Plant Taxonomy, 2014)
Not available DOI: http://dx.doi.org/10.3329/bjpt.v21i2.21362 Bangladesh J. Plant Taxon. 21(2): 199-202, 2014 (December)